Normally‐off GaN MOSFETs with high‐k dielectric CeO2 films deposited by RF sputtering. Issue 2 (20th January 2014) - Ogawa, Hiroki; Okazaki, Takuya; Kasai, Hayao; Hara, Kenta; Notani, Yuki; Yamamoto, Yasuhiro; Nakamura, Tohru
Abstract This paper describes normally‐off GaN MOSFETs with high‐k dielectric CeO2 films made by ion implantation. Ion implantation process reduces sheet and contact resistances of source and drain regions of this device. To obtain high Idss and gmmax, high‐k dielectric CeO2 was used as gate oxide films for GaN MOSFETs for the first time. Nitrogen ion implantation isolation processes were also adopted to fabricate isolation region. Normally‐off GaN MOSFETs with Idss of 350 mA/mm, gmmax of 40 mS/mm and threshold voltage of +0.5 V were obtained. The high Idss and normally‐off mode show the potential and advantages of GaN MOSFETs for high voltage operations. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)